Nondestructive analysis of alterations of Chinese jade artifacts from Jinsha, Sichuan Province, China - Bao, Yi (Sci Rep, 2020)
Jade, which is one of the most characteristic materials constituting Chinese artifacts, signifies cultural differences between ancient Chinese and western civilizations. One of the most important typical characteristics of ancient jade artifacts recovered through archeological excavations is color alterations due to human activity and natural weathering, which has led to an area of intensive research in archeology. “Alteration” refers to chemical component and structural changes in jade artifacts caused by human activity and natural weathering, which is different from the term in geology. In this study, Raman spectroscopy was used to analyze six color alterations on ancient jade artifacts unearthed from the Jinsha Site in Sichuan Province, a region famous for artifacts with colorful alterations. The colorful alterations were observed to originate from corrosion products of bronzeware. The green, black, yellow, blue, purple, and white alterations were due to malachite, tenorite, pyromorphite, azurite, diaboleite, and cassiterite, respectively. Meanwhile, organic matter and hypertoxic arsenolite were first found on ancient jade artifacts.